IMPROVING SKI LEARNING OUTCOMES BASED ON CLASS MANAGEMENT USING A WHOLE GROUP DISCUSSION APPROACH - Hunaidah, Hunaidah (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2024)
Teacher competence in implementing classroom management functions based on student activity, as well as student interest and active participation in the learning process, is one of the factors that can influence the achievement of learning objectives and improve student learning outcomes, so innovative learning management is needed. The purpose of this study is to examine how classroom management using the whole group discussion technique and increasing the History of Islam (SKI) learning achievement of class V students of Madrasah Ibtidaiyah (MI) Attaqwa 19 Bogor sero Bekasi. This research used an experimental method with a classroom action research (PTK) approach applied to 80 students in class V MI 19 Bogor Sero Bekasi, who were divided into two classes, through the use of Simple Random Sampling Techniques. Shows that there is an increase in SKI learning results after conducting experiments using a classroom management approach based on the use of whole group discussion techniques, and the results of rxy and t calculations show t-count is 4.352 while t-table is 1.685954; this shows t-count is greater than t-table, meaning there is a significant influence So, classroom management using the Whole Group Discussion Technique has a significant influence on student learning outcomes in SKI subjects with a Gain Score of 63.6, meaning there is a significant increase between the experimental class and the control class. This research can be used as a reference for teachers to improve student learning outcomes.